2021
DOI: 10.1002/macp.202000433
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Cellulose from a Switchable Ionic Liquid: Toward More Sustainable Cellulose Fibers

Abstract: A CO2 switchable solvent system is investigated to find an environmentally friendlier way to produce man‐made cellulose fibers. Cellulose solutions with concentrations from 2 wt% to 8 wt%, based on derivative and non‐derivative dissolution approaches, are investigated. Three different switchable solvent systems are tested. After accessing the stability of the produced cellulose solutions, their regeneration is investigated using different alcoholic coagulation media. In order to find a suitable coagulation med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The key factor for the regulation of the physic process is the double diffusion of the co-solvent and the nonsolvent between the coagulation bath and the spinning dope, which can be simply controlled by the temperature and the composition of the coagulation bath and the residence time of the gel-state fiber in the coagulation bath. As a nonsolvent for cellulose, H 2 O was widely used as a coagulation bath for the regeneration of cellulose in wet spinning for many cellulose dissolution systems, such as viscose rayon, NaOH/urea aqueous solution, ,, ionic liquid, , and NMMO. ,, In the case of the CO 2 switchable solvent, although previous studies have used not only H 2 O but also alcohol as a coagulation bath for the regeneration of cellulose for the preparation of cellulose film and fiber, the regenerated cellulose films prepared from alcohol were amorphous, which was not favorable for the preparation of cellulose fiber with good mechanical properties. Therefore, we started our exploration by employing H 2 O as the coagulation bath for wet spinning of cellulose based on the CO 2 switchable solvent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The key factor for the regulation of the physic process is the double diffusion of the co-solvent and the nonsolvent between the coagulation bath and the spinning dope, which can be simply controlled by the temperature and the composition of the coagulation bath and the residence time of the gel-state fiber in the coagulation bath. As a nonsolvent for cellulose, H 2 O was widely used as a coagulation bath for the regeneration of cellulose in wet spinning for many cellulose dissolution systems, such as viscose rayon, NaOH/urea aqueous solution, ,, ionic liquid, , and NMMO. ,, In the case of the CO 2 switchable solvent, although previous studies have used not only H 2 O but also alcohol as a coagulation bath for the regeneration of cellulose for the preparation of cellulose film and fiber, the regenerated cellulose films prepared from alcohol were amorphous, which was not favorable for the preparation of cellulose fiber with good mechanical properties. Therefore, we started our exploration by employing H 2 O as the coagulation bath for wet spinning of cellulose based on the CO 2 switchable solvent.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated in previous studies that DMSO and DBU can be recovered after regeneration of cellulose. ,, Therefore, we also designed and performed solvent recovery after wet spinning (Figure S4). Our results showed that the recovery yields of DMSO and DBU were 86.6 and 42.4%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, progress has been made by Meier, who introduced a more sustainable process for esterification of cellulose in a switchable 1,8diazabicyclo[5.4.0]undec-7-en (DBU)/CO 2 solvent system that holds promise for the development and processing of advanced cellulose-based plastics. [165][166][167][168][169][170][171][172][173] Tough and transparent cellulose nanopaper with high porosity was derived from aqueous dispersions of cellulose nanofibrils. [174][175][176][177][178][179] Advances in nanofibrillated cellulose production and its potential applications, ranging from nanopaper to nanocomposites, coatings, and food packaging, have been addressed by several reviews.…”
Section: Bio-based Plastics Extracted From Naturementioning
confidence: 99%
“…As a result, the dissolution of cellulose is achieved. Thereafter, a series of studies showed that this system can be used for the homogeneous chemical modification of cellulose for the synthesis of cellulose esters 33,34 and cellulose carbonates, [35][36][37] and for the processing of cellulose to prepare regenerated cellulose films, 38,39 fibers, 40,41 and aerogels. 42 Interestingly, in our previous study, we found that this system can be considered as "organic viscose", because of its similarity to the classical viscose sytem.…”
Section: Introductionmentioning
confidence: 99%